2020
DOI: 10.1109/twc.2020.2999339
|View full text |Cite
|
Sign up to set email alerts
|

Wake-Up Scheduling for Energy-Efficient Mobile Devices

Abstract: Recently, discontinuous reception mechanisms (DRX) and wake-up schemes (WuS) have been proposed to enhance the energy efficiency of 5G mobile devices and prolong the battery lifetime. The existing DRX and WuS use commonly pre-configured parameters that cannot be adjusted dynamically. In this paper, a novel wake-up scheduling (WuSched) concept is introduced to further improve the energy efficiency of WuS-enabled mobile devices while controlling the buffering delay in a dynamic manner. The main idea of WuSched i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Similarly, the authors in [232] shed some light on BLEcompatible sensor devices enriched with a WUR, and their results demonstrate EE gains in low-latency applications (under 2s). In [233], the authors optimize operational parameters, determined by BS at the beginning of the session, to save energy. Meanwhile, an accurate traffic forecasting model is proposed in [218] to optimize the wake-up parameters, achieving up to 35% EC reduction.…”
Section: ) State-of-the-artmentioning
confidence: 99%
“…Similarly, the authors in [232] shed some light on BLEcompatible sensor devices enriched with a WUR, and their results demonstrate EE gains in low-latency applications (under 2s). In [233], the authors optimize operational parameters, determined by BS at the beginning of the session, to save energy. Meanwhile, an accurate traffic forecasting model is proposed in [218] to optimize the wake-up parameters, achieving up to 35% EC reduction.…”
Section: ) State-of-the-artmentioning
confidence: 99%
“…In the WuS, the UE monitors narrowband channel for wake-up signalling to get the message for the arrival of packet(s). Recently, wake-up scheduling was proposed to improve the power saving of WuS enabled UE under predefined delay [15].…”
Section: State Of the Artmentioning
confidence: 99%
“…Numerous mathematical analysis are proposed to model the DRX mechanism by several researchers. Most of these studies considered that the data arrival follows Poisson process [7,[14][15][16]. To match with the realistic scenario, where data packets arrive in bulk, compound Poisson process is the best suited to model the arrival process [9].…”
Section: State Of the Artmentioning
confidence: 99%
“…If we could accurately forecast utilization at such a small timescale (every millisecond), we could make real-time decisions to switch off cells and achieve larger energy savings. In fact, prediction of packet arrivals in each TTI has been found to be feasible in [27,28]; however, an analysis of the PRB utilization at this granularity has not been studied so far. Our analysis has found that the utilization trace at the TTI level for each pair of coverage and capacity cells is actually a stationary time series, without any trend or seasonality -thus, it does not have a predictable pattern in the long-term [29].…”
Section: A Metrics and Granularitymentioning
confidence: 99%
“…Trinh et al [27] propose the use of LSTM networks to predict traffic (in Mbps) at the TTI-level (1 ms) and find that LSTM outperforms ARIMA models. More recently, Rostami et al [28] present an LSTM network to predict traffic (packet arrival times) in the next 1 to 30 TTIs. They find that the prediction accuracy is high when predicting arrivals up to 15 TTIs ahead.…”
Section: Related Workmentioning
confidence: 99%